Pengaruh Financial Socialization, Financial Knowledge dan Financial Experience Terhadap Financial Management Behaviour (Studi pada Mahasiswa Universitas Islam Malang) - Halimah, Faridatul; Mardani, Ronny Malavia; Bastomi, Mohamad (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract This research aims to analyze and explain the influence of Financial Socialization, Financial Knowledge and Financial Experience on Financial Management Behaviour among Students at the Islamic University of Malang. The sample used ini this research was 96 respondents obtained from the Slovin formula using probability sampling techniques. The data analysis method used ini this research is quantitative data analysis using multiple linier regression analysis. The data testing used is partial hypothesis testing. The results of this research show that partially the Financial Socialization variable has a significant effect on the Financial Management Behaviour of Islamic University of Malang Students, the Financial Knowledge variable has a significant effect on the Financial Management Behaviour of Islamic University of Malang Students, and the Financial Experience variable has no significant effect on the Financial Management Behaviour of Islamic University of Malang Students. Keywords: Financial Socialization, Financial Knowledge, Financial Experience and Financial Management Behaviour.